2010
DOI: 10.1007/s10637-010-9542-z
|View full text |Cite
|
Sign up to set email alerts
|

The histone deacetylase inhibitor butyroyloxymethyl diethylphosphate (AN-7) protects normal cells against toxicity of anticancer agents while augmenting their anticancer activity

Abstract: The histone deacetylase inhibitor (HDACI) butyroyloxymethyl diethylphosphate (AN-7) has been shown to synergize doxorubicin (Dox) anticancer activity while attenuating its cardiotoxicity. In this study we further explored the selectivity of AN-7's action in several cancer and normal cells treated with anticancer agents. The cells studied were murine mammary 4T1, human breast T47D and glioblastoma U251 cancer cell lines, neonatal rat cardiomyocytes, cardiofibroblasts and astrocytes, and immortalized cardiomyocy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
26
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 40 publications
4
26
0
Order By: Relevance
“…Our group previously demonstrated the protective effect of AN-7 against Dox-toxicity in cardiomyocytes and astrocytes and AN-7 augmentation of Dox's anticancer activity against breast carcinoma and glioblastoma cells in vitro [12], [15]. The aim of the present study was to substantiate our earlier findings in vivo and to investigate the underlying cellular and molecular modifications responsible for this disparity.…”
Section: Discussionsupporting
confidence: 54%
See 2 more Smart Citations
“…Our group previously demonstrated the protective effect of AN-7 against Dox-toxicity in cardiomyocytes and astrocytes and AN-7 augmentation of Dox's anticancer activity against breast carcinoma and glioblastoma cells in vitro [12], [15]. The aim of the present study was to substantiate our earlier findings in vivo and to investigate the underlying cellular and molecular modifications responsible for this disparity.…”
Section: Discussionsupporting
confidence: 54%
“…Previously, we have shown that AN-7 synergistically increased Dox cytotoxicity against 4T1 cells, and conversely, it protected cardiomyocytes against Dox toxicity [12]. In an attempt to understand the basis for this disparity, we examined the manner by which AN-7, Dox and AN-7+Dox affect the total cellular activity of HDACs classes I and II in these cancerous and non-cancerous cells.…”
Section: Resultsmentioning
confidence: 95%
See 1 more Smart Citation
“…7). Further evaluation of the mechanisms engaged in ADs-mediated neuroprotection against Dox toxicity would be very important from the clinical point of view since glia cell damage occurs during chemotherapy and concomitantly with neuronal cell damage participate in neurocognitive impairments observed in patients after long-term chemotherapy (Bigotte and Olsson 1983; Moriuchi et al 1996; O’Farrell et al 2013; Tarasenko et al 2012). Regarding the protective effects of Tian in glia cells, it has been shown that Tian (10–100 μM) attenuated the gp120-evoked cell death in glia cells and this effect was connected with attenuation of caspase-3 activity, DNA fragmentation and the influence of this drug on the expression and activity of glutamine synthase (GS), transcription factor NFκB, and nitric oxide system (NO, cNOS, iNOS) (Janda et al 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Arterial smooth muscle cells from mice overexpressing a nonfunctional form of Nox4 showed decreased TSP1 mRNA and protein expression (275), suggesting that Nox4 is a proximate driver of TSP1 expression. Fibroblasts treated with doxorubicin displayed increased ROS levels and TSP1 protein expression (269).…”
Section: Tsp1 and Ros Signaling In Vivomentioning
confidence: 96%